Features of reforestation in the longterm agricultural use of geosystems of the Tunkinskaya depression. (November 2019) - Atutova, Zh V
Abstract: The paper focuses on identifying the features of natural reforestation after abandonment of agricultural land. That was achieved by the annual monitoring (2014 to 2018) of current state of 22 fallow land sites within the most agrarian-developed areas of the Tunkinskaya depression (Republic of Buryatia). Geobotanical analysis of the species composition of woody and grass covers of fallow lands was carried out. The main options for overgrowing fallow lands were determined. This is a restoration through birch, pine or mixed undergrowth, as well as meadow succession. Natural reforestation on fallow lands flows more intensively around the perimeter of the fields. The species composition of the undergrowth is identical to the forest canopy of the adjacent forests. In the grass cover of fallow lands in most cases there is a dominance of meadow species. In the grass cover of the surrounding forests, forest species prevail. Our research confirmed the dependence of distribution intensity of tree undergrowth on the degree of remoteness from the forests surrounding the abandoned lands. A decrease in the excess growth of tree species was observed with increasing distance from the periphery of the field to its centre.